RELEVANSI DAKWAH SUFISTIK IMAM GHAZALI BAGI MASYARAKAT INDONESIA - Much Wasith Achadi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
In today's contemporary era, one of the many problems experienced by the world community is the spiritual restlessness. Spiritual restlessness is not only felt by the Western people, but also by the people of Indonesia. According to some experts, to address the problems that plague contemporary society, it is very possible using sufistic propaganda to answer the crisis of meaning. Here, sufistic propagada means delivery of sufistic discourses or esoteric dimensions of islamic doctrine to the public. Because contemporary human problems are spiritual emptiness, then it should be treated with something that is spiritual. This paper will discuss the relevance Imam Ghazali‟s propaganda for Indonesian contemporary society.